Model development for prevention of malaria in Kalasin Province - วิริยะวิภาต, ชื่นพันธ์; กลางบุรัมย์, วันทนา (Disease Control Journal, 2015)
The main objectives of this study were to study factors related to preventive behavior of people towards malaria and model development for prevention of the disease. The study was conducted in three sub- districts namely Pasawoei, Mahachai and Sangbadan of Somdej district, Kalasin province. Both quantitative and qualitative methods were used in the study. In the first step, simple random sampling of 200 populations was performed. Questionnaire was designed for data collection of preventive behavior towards malaria and the analysis was performed using the multiple logistic regression statistics. Results of the first step revealed that factors related to malaria preventive behavior included public mind, and inspiration toward self-care of health. Individuals with strong public mind showed 2.90 times greater malaria preventive behavior compared with those without public mind (OR = 2.90 , 95% Cl = 0.24-0.88). In the second step, combination of qualitative and quantitative research with integration Participation Appreciation Influence Control (PAIC) was applied, of which 11 villages were selected on the voluntary basis for a model development of prevention of malaria. The evaluation of achievement of such model was performed by analysis of data using descriptive statistic and multivariate analysis of variance. Results showed that strategies for malaria control and preven¬tion were inclusion of village health volunteers including the youths to work as village committee for planning and providing health education on malaria prevention to the villagers. This was performed under the supervi¬sion and support of sub-district administration, sub-district health promotion hospital, and center for vector- borne disease control. The evaluation of achievement of model development revealed that the villagers in the three sub-districts conformed effectively to the malaria preventive measures (household index (HI) for mos¬quito larva = 0 in every village). The number of new malaria cases in 2012 and 2013 were declined by 99.60 and 87.9096, respectively. In conclusion, results of the study suggest that in all malaria endemic areas, it is necessary to find appropriate model or intervention for effective prevention and control of the disease on the basis of community participation. These strategies should also be applied on other endemic areas.